Analisis Pengaruh Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Hijab Rabbani (Studi Kasus Outlet Rabbani Jombang) - Lina Auliyana (BIMA : Journal of Business and Innovation Management, 2020)
The purpose of this research is to find presence or absence the influence of Brand Image and the quality of product on the decision to purchase the hijab rabbani ( case study on the Rabbani outlet in Jombang). Type of this research is using quantitative method. Sampling technique that using by the research is non probably sampling techniques in a way compare incidental sampling with a sample of 80 costumers. Data collection in this research is using questionnaire, interview, documentation, and observation. In the process of data analysis the researcher using statistical method to validity and reability the data, classic assumption test, hypothesis with multiple linear formula. Finding of the research indicate that : (1) basicly, brand image give impact positivity in Rabbani Hijab decisions at Rabbani Jombang Outlet. (2) The quality of product has significant effect in hijab rabbani distributions. (3) Brand Image and the quality of product has influence in towards purchases rabbani hijab at Rabbani Jombang Outlet.